A realistic scooter rebalancing system via metaheuristics - Fernandes, Guilherme (2020)
This paper addresses a realistic electric scooter rebalancing task that includes business rules (e.g., time constraints, available truck fleet). We explore an integer encoding approach and three metaheuristics (hill climbing, simulated annealing, genetic algorithm), discussing the obtained results, current limitations and future work directions.